Estudio de factibilidad para la creación de una empresa de servicios de turismo de aventura en el distrito de Buenaventura (2013)
Pacific extreme is an innovative company. The incursion in the tourism sector generates diversification of the district’s economy. This investigation allows the development, application and practice of the knowledge acquired in the course of the career. For that the next objective was planned: Determinate the viability of this project. To achieve it, the market was determined; characteristics and acceptance of services, technical and infrastructure needs were indicated, administrative requirements were established, financial viability was proven, and last we studied the environmental and social impact that the company generates. The research was framed in theories of modernization, the theory of change, and the theory of competitiveness of Alvarez and Garcia. To obtain the data studio exploratory type was used, descriptive obtaining a sector diagnosis, using Porter’s diamond and inductive method. The tools and techniques used was the survey of the tourists, where the analysis was done to establish the degree of acceptance of adventure sports, since to the majority it seemed attractive and good. The social contribution is to generate employment for the habitants of the sector. The company has a significant market opportunity, the tourism plans of adventure are interesting and striking, plans that have not been explored in the city. The financial evaluation shows the viability of the project, reporting earnings from the first year of operations.